Expression and functional analysis of novel stress-involved transcription factor NLI-IF in rice - Phuong, Nguyen Duy; Tuteja, Najaren; Hoi, Pham Xuan (Academia Journal of Biology, 2013)
We reported previously that one transcription factor NLI-IF (Nuclear LIM interactor-interacting factor)-encoded cDNA clone was identified by yeast one hybrid assay, using 2 target sequences JRC0528 and JRC0332. In this paper we reported some results of in vivo analysis of NLI-IF. The core sequence-specific DNA binding ability of NLI-IF was identified, using yeast one hybrid assay. To identify of protein-protein interaction, the rice stress-treated cDNA library was screened using yeast two hybrid assay and 8 cDNA clones were isolated. These results support to our expectation that transcription factor NLI-IF is involved in stress responses in plant.